Model Indeks Kekuatan Negara dengan Regresi Beta: Analisis Pengaruh Stabilitas Ekonomi, Demografi, dan Infrastruktur Teknologi Terhadap Kemampuan Pertahanan dan Keamanan - Muflih Al Faruq; Alief Syahnur Almaida; Khoirul Fajri; Anggit Naufal Nararya Fawwaz Tyaga (Populer: Jurnal Penelitian Mahasiswa, 2025)
Power Index is a strategic indicator measuring a nation's military, economic, and geopolitical capabilities, closely tied to national defense and security. This study examines key factors such as currency exchange rates, GDP, education levels, and technology penetration in shaping the Power Index. Economic stability underpins defense development, while advanced education and digital infrastructure drive innovations in military technology and cybersecurity. Developed countries dominate defense capabilities due to robust technological infrastructures, while developing nations show potential through investments in education and technology. Beta distribution regression, with its suitability for bounded variables, was utilized to model the Power Index. The study provides insights into the interplay between economic, educational, and technological factors, supporting strategic policymaking to strengthen national defense in a dynamic global landscape.